"How to Live a Good Life": Self-managing Reproductive Health for Adolescent Refugees in Kampala. Issue 1 (1st June 2022) - Palattiyil, George; Zuntz, Ann-Christin; Nair, Harish; Bukuluki, Paul; Sebba, Kalyango Ronald
Abstract: This article provides an ethnographically informed critique of the humanitarian self-management model that informs reproductive health trainings for young urban refugees in Kampala, Uganda. It draws on interviews with 16 adolescent refugees, as well as policymakers, aid workers and health care professionals in Kampala in April 2019. We found that reproductive health education training sessions are a site of gendered learning where displaced boys and girls gain an understanding of what it means "how to live a good life" and how to become marriage material. Their focus on self-control also reflects a wider shift in humanitarianism toward female empowerment as a tool of neoliberal governance. In a low-resource context, however, "self-managing" one's reproductive health takes on a different meaning, as displaced adolescents weigh up opportunities for short-term income from transactional sex with imagined reproductive futures elsewhere.